DETERMINANT OF STUNTING AMONG CHILDREN 15-49 MONTHS IN ZAMBIA (ZAMBIA DHS ANALYSIS 2018) - Ulfa Al Uluf; Trias Mahmudiono; Mahmudah Mahmudah; Soenarnatalina Melaniani (Universitas Airlangga, 2022)
One of the countries with a high prevalence of stunting in East Africa is Zambia. Globally, 22% of children under 5 years old are stunted or 149.2 million children in 2020. Stunting prevalence in Zambia remains above 35% in children under 5 years old at the national level. Research in Zambia about determine of stunting is still few and limited. The aim of this study was to identify determine with stunting in children aged 0-59 months in Zambia. The method used is observational in secondary data from the 2018 Demographic and Health Survey (DHS) in Zambia. Mothers of toddlers are Respondents aged 15 - 49 years and having toddlers aged 15 - 49 months. The sample size used in this study was 3804 mothers with children under five. Bivariate analysis using Chi-Square test and multivariate analysis using Multiple Logistic Regression. The results showed that the factors related to stunting were maternal age (p=0.164), marital status (p=0.187), wealth index (p=0.149), age of children under five (p=0.164) and order of children (p=0.077). Marital status OR 2.724 (0.846-8.769) the most influence the occurrence of stunting in children under five. The implication of this study is the more mothers who never married, the greater the risk of stunting.